1999
DOI: 10.1108/eb022816
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Styles in Conflict Management and Effectiveness

Abstract: Access to this document was granted through an Emerald subscription provided by emeraldsrm:463575 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
79
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 47 publications
8
79
0
5
Order By: Relevance
“…Previous research concluded that ERs tend to combine cooperative and competitive behaviors (Elgoibar 2013;Munduate et al 1999). However, such combinations usually represent either a more cooperative or competitive approach (Van de Vliert et al 1995).…”
Section: Type Of Conflict and Conflict Managementmentioning
confidence: 99%
“…Previous research concluded that ERs tend to combine cooperative and competitive behaviors (Elgoibar 2013;Munduate et al 1999). However, such combinations usually represent either a more cooperative or competitive approach (Van de Vliert et al 1995).…”
Section: Type Of Conflict and Conflict Managementmentioning
confidence: 99%
“…This combination can include a more cooperative or competitive approach and is known as Conglomerate Conflict Behaviour ( Van de Vliert et al, 1995). It has been shown that combining conflict behaviours drives towards effectiveness (Munduate et al, 1999: Van de Vliert et al, 1997. The main explanation for this conglomerate pattern of conflict behavior is given by the perception that conflicts are often mixed-motive situations (Euwema and Van Emmerik, 2007).…”
Section: Conflict Managementmentioning
confidence: 99%
“…As mentioned above, ERs tend to combine cooperative and competitive styles (Elgoibar 2013;Euwema and Van Emmerik 2007;Van de Vliert et al 1995). This combination can include a more cooperative or competitive approach and here we appreciate differences between the countries (Munduate et al 1999). For example, in Denmark, Germany and Estonia, ERs show a more cooperative pattern (relatively high on cooperation, and relatively low on competition), whereas in Belgium, the UK and Spain, ERs tend towards a more competitive pattern, with competitive behavior more prevalent than cooperative behavior.…”
Section: Frequency Of Conflicts Between Management and Ersmentioning
confidence: 99%